The Shifting Scales of Western U.S. Landfalling Atmospheric Rivers Under Climate Change. Issue 17 (5th September 2020) - Rhoades, Alan M.; Jones, Andrew D.; Srivastava, Abhishekh; Huang, Huanping; O'Brien, Travis A.; Patricola, Christina M.; Ullrich, Paul A.; Wehner, Michael; Zhou, Yang
Abstract: Atmospheric rivers (ARs) can be a boon and bane to water resource managers as they have the ability to replenish water reserves, but they can also generate million‐to‐billion‐dollar flood damages. To investigate how anthropogenic climate change may influence AR characteristics in the coastal western United States by end century, we employ a suite of novel tools such as variable resolution in the Community Earth System Model (VR‐CESM), the TempestExtremes AR detection algorithm, and the Ralph, Rutz, et al. (2019, https://doi.org/10.1175/BAMS‐D‐18‐0023.1 ) AR category scale. We show that end‐century ARs primarily shift from being "mostly or primarily beneficial" to "mostly or primarily hazardous" with a concomitant sharpening and intensification of winter season precipitation totals. Changes in precipitation totals are due to a significant increase in AR (+260%) rather than non‐AR (+7%) precipitation, largely through increases in the most intense category of AR events and a decrease in the interval between landfalling ARs. Plain Language Summary: Atmospheric rivers are central to water resource management in the western United States. Anthropogenic climate change has and continues to alter these storms, which has a cascade of societally relevant impacts. We evaluate how end‐century atmospheric river behavior is altered, assuming little‐to‐no carbon mitigation occurs. To do this, we use a state‐of‐the‐art global climate simulation that allows us to connect global‐to‐regional scales and, compared with conventional global climate models, better represent the interactions between atmospheric rivers and mountains when they make landfall. To isolate changes in atmospheric river behavior in our simulations, we use a newly developed atmospheric river detection algorithm and category scale devised to communicate risk more clearly. Using these tools, we find that by end‐century atmospheric river character shifts from being "mostly or primarily beneficial" to "mostly or primarily hazardous." This results in increased precipitation totals, primarily from the most hazardous atmospheric rivers, resulting in a sharpening and intensification of the water year. Some end‐century atmospheric rivers exceed the highest levels of the category scale; however, we do not find that any single storm produces significantly more precipitation. Therefore, the increased precipitation is due to an increase in the number of hazardous atmospheric rivers that more regularly occur back‐to‐back. Key Points: Atmospheric rivers in variable‐resolution‐enabled Community Earth System Model simulations are validated and projected under climate change Shifts in end‐century atmospheric river character lead to sharper, more intense winter season precipitation totals in the coastal western United States No single end‐century atmospheric river event produces unprecedented precipitation totals, yet totals from sequential atmospheric rivers do